Quantitative evaluation of variables to student success in a mastery learning baccalaureate nursing programme - Marie Rolf; Margaret Kroposki; Susan Watson (Wiley, 2019)
Abstract Aim This study evaluated the relationship of student input and throughput variables in a mastery learning baccalaureate nursing programme to licensure success. Design This study used a quantitative, correlational design. Methods Retrospective analysis of records of 367 graduates over a 6‐year period tested the relationship of pass rate on the licensing examination to six variables: overall pre‐admission grade point average, entrance assessment scores, interview scores, remediation, programme length and exit assessment using point‐biserial correlations, and chi‐square analysis and logistic regression analysis. Results Overall pre‐admission grade point average, entrance assessment scores, interview scores and exit assessment scores were positively correlated with student success. Although remediation and programme length were not correlated with success, 87% of the students participated in remediation. Most students (95%) successfully passed the Registered Nurse licence examination on their first attempt. While specific criteria were related to student success, further research is needed to determine the role of remediation.